(untitled) (Eurasian Journal of Ecology, 2018)
The article gives a geobotanical description and a floristic analysis of communities with the participation of the rare and relict species Alnus glutinosa in condition of Aktobe region. The aim of the study is to provide a geobotanical assessment of the current status of a rare, relict species of the Alnus glutinosa population, which was included in the Red Data Book of Kazakhstan. At present, the flora of the Aktobe region is not sufficiently studied. Conservation of the biodiversity of the Aktobe region flora is one of the most topical issues. The disappearance of the species has a great impact on the ecology of the environment. Therefore, the protection of rare and relict species is of particular importance. The Alnus glutinosa plant is a relict of the Quaternary period. An ornamental plant used in forest protection. In Aktobe region, due to the lack of grazing, felling of trees, using as fuel and the emergence of uncontrolled tourism and at the same time due to the lack of natural renewal of the area, these consequences lead to a quantitative reduction in the species. In this regard, it is necessary to study the species and organize protection and conservation measures. The results of the study showed that the plant Alnus glutinosa is rarely found in the flora of Kazakhstan and also the distribution areas are reduced. Of the three investigated points, plants from 24 families were identified Key words: Alnus glutinosa, life form, population, flora, tier.